2017
DOI: 10.1177/0194599817697054
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of GJB2 Mutation Status for Hearing Outcomes of Pediatric Cochlear Implantation

Abstract: Objective To systematically review and quantify current evidence regarding the association of GJB2 mutation status with outcomes of pediatric cochlear implantation. Data Sources PubMed, Embase, and the Cochrane Library were searched for "GJB2,""pediatric hearing loss," and "cochlear implantation" and their synonyms, with no language restrictions, until December 2, 2015. Review Methods Studies were included that investigated the status of GJB2 mutation and its predictive value for outcomes of pediatric cochlear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
0
19
2
1
Order By: Relevance
“…Previously published data were based on the analysis of a limited number of patients wherein the most numerous group was almost four times smaller than ours (40 vs. 149) [8,31]. Moreover, there was a large variation in the time of implantation, ranging from 1 to even 14 years of age [8,32]. The patients described in a single study have often been exposed to different environmental factors, such as different lengths of auditory deprivation, as well as having different levels of natural ability to acquire auditory skills [3].…”
Section: Possible Explanations For Uncertain Data From the Literaturecontrasting
confidence: 55%
See 2 more Smart Citations
“…Previously published data were based on the analysis of a limited number of patients wherein the most numerous group was almost four times smaller than ours (40 vs. 149) [8,31]. Moreover, there was a large variation in the time of implantation, ranging from 1 to even 14 years of age [8,32]. The patients described in a single study have often been exposed to different environmental factors, such as different lengths of auditory deprivation, as well as having different levels of natural ability to acquire auditory skills [3].…”
Section: Possible Explanations For Uncertain Data From the Literaturecontrasting
confidence: 55%
“…All patients were treated in one medical center. Previously published data were based on the analysis of a limited number of patients wherein the most numerous group was almost four times smaller than ours (40 vs. 149) [8,31]. Moreover, there was a large variation in the time of implantation, ranging from 1 to even 14 years of age [8,32].…”
Section: Possible Explanations For Uncertain Data From the Literaturecontrasting
confidence: 51%
See 1 more Smart Citation
“…For patients with severe phenotypes who possess GJB2 mutations, genetic information would aid in decision making regarding CI, as their hearing loss is of cochlear origin and they, therefore, would be good candidates for CI. The present literature review indicates that the majority of papers showed significant improvement in speech performance in GJB2 ‐related deafness patients and the remaining papers showed equivalent results between GJB2‐ related deafness and non‐ GJB2 deafness (for review; Abdurehim et al, ; Nishio and Usami, ). The difference in these results is probably due to patient selection bias.…”
Section: In Patients With Specific Genetic Backgroundsmentioning
confidence: 76%
“…It is estimated that nearly 50% of pre-lingual deafness cases have a genetic connection. 1,10 In 70% of those cases, it is related to a non-syndromic mutation, 80% being of recessive inheritance, 15% of dominant inheritance and 1% linked to the X cromossome. 7 The most common mutation occurs in the GJB2 gene, responsible for coding the connexin 26.…”
Section: Discussionmentioning
confidence: 99%